Spontaneous Coronary Artery Dissection - صالح منتجب (Latakia University Journal -Medical Sciences Series, 2021)
Spontaneous coronary artery dissection (SCAD) is an infrequent and often missed diagnosis among patients presenting with acute coronary syndrome (ACS). Unfortunately, SCAD can result in significant morbidities such as myocardial ischemia and infarction, ventricular arrhythmias and sudden cardiac death. Lack of angiographic recognition from clinicians is a major factor of under-diagnosis. With the advent of new imaging modalities, particularly with intracoronary imaging, there has been improved diagnosis of SCAD. The aim of this paper is to review the epidemiology, etiology, presentation, diagnosis and management of SCAD.